Metasurface-generating high purity narrow linewidth cylindrical vector beams: power scaling and its limitation - Li, Haokun; Xie, Lianghua; Zhang, Chun; Tao, Rumao; Shu, Qiang; Li, Min; Shen, Benjian; Feng, Xi; Xu, Lixin; Wang, Jianjun (Frontiers in Physics, 2023)
1.89 kW cylindrical vector beams (CVBs) at 1,064 nm with the 3 dB linewidth being about 0.08 nm have been generated from a narrow linewidth all-fiber linearly-polarized laser by metasurface extra-cavity conversion. At the maximum output power, the transmission efficiency, mode purity of radially polarized cylindrical vector beams (RP-CVBs) are 97% and 92.7%, respectively. To the best of our knowledge, this is the highest power of narrow linewidth CVBs generated from fiber laser. The temperature of the metasurface is moderate, and the maximum temperature is 75.5°C at 1.89 kW, which means that the system can be further power scaled. The evolution of mode purity has been analyzed numerically, and the influence of high-order modes (HOM) in laser source and thermal effects of metasurface has been calculated, which reveals that the presence of high-order modes and the temperature rise of metasurface degrade the mode purity of the CVBs. Among them, HOM causes a degradation of 1.68%, thermal lensing effect contributes 2.32%, and the microstructure variation of the metasurface contributes the remaining 3.3%.